2014
DOI: 10.1016/j.meegid.2014.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary genomics of Borrelia burgdorferi sensu lato: Findings, hypotheses, and the rise of hybrids

Abstract: Borrelia burgdorferi sensu lato (B. burgdorferi s.l.), the group of bacterial species represented by Lyme Disease pathogens, has one of the most complex and variable genomic architectures among prokaryotes. Showing frequent recombination within and limited gene flow among geographic populations, the B. burgdorferi s.l. genomes provides an excellent window into the processes of bacterial evolution at both within- and between-population levels. Comparative analyses of B. burgdorferi s.l. genomes revealed a highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 120 publications
(257 reference statements)
0
49
0
Order By: Relevance
“…mayonii strains belong to the same allele group, termed here OspC type Bmayo1. Phylogenetic analysis of a ~6.5 kbp region of cp26, shown previously to be relatively free from recombination in Bbsl genospecies [22], is shown in Fig 4. The two B .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…mayonii strains belong to the same allele group, termed here OspC type Bmayo1. Phylogenetic analysis of a ~6.5 kbp region of cp26, shown previously to be relatively free from recombination in Bbsl genospecies [22], is shown in Fig 4. The two B .…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic analysis of a ~6.5 kbp region of cp26 from Bbsl genospecies was performed using MEGA6 [36]. Briefly, DNA sequences were aligned using MUSCLE, maximum likelihood trees generated using 4 discrete gamma categories and rooted at the midpoint based on Qiu et al 2014 [22], followed by 1000 bootstrap replicates. Sequences included in the phylogenetic analysis were retrieved from GenBank.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive work on these sequence-based characteristic markers on other groups of prokaryotes have shown that these markers possess a high degree of predictive ability to be identified in other group members, for which no sequence information may be available at the time (reviewed in [76,77]). With the more explicit division of the Borreliaceae species into two genus-level groups, attention can be focused on unique genetic and molecular characteristics that differentiate the two groups of microbes [78]; the described characteristics in other groups of bacteria have been found to play important and generally essential roles [79]. For Borreliaceae species, some of the CSIs that distinguish between the RF and LD groups are in proteins, such as the flagellar motor switch protein FliM, chemotaxis proteins CheY and CheW, and cell shape-determining protein MreB [4], that Margos et al [7] write that 'splitting the genus does not provide any assistance as far as clinical evaluation is concerned' and further that '[it] does not help end user communities including in clinical medical practice, public health, or those studying the ecology of the bacteria'.…”
Section: Possible Adverse Consequences Of the Reclassification Of Memmentioning
confidence: 99%
“…One Borrelia species, Borrelia bissettii, is found overlapping the distribution of B. burgdorferi ss in the US and in areas of Europe (Margos et al, 2012). The B. bissettii spirochaete is phylogenetically closely related to the human pathogenic B. burgdorferi ss species (Qiu & Martin, 2014). To date, three studies have demonstrated molecular detection of B. bissettii (Girard et al, 2011;Rudenko et al, 2008Rudenko et al, , 2009 in human clinical samples.…”
Section: Introductionmentioning
confidence: 99%